THE INFLUENCE OF TEACHER CONTROL ON MEMORIZATION OF ISLAMIC BOARDING SCHOOL STUDENTS AT PONDOK DARUL FITHRAH GRAJEGAN, TAWANGSARI DISTRICT, SUKOHARJO REGENCY - Az Zuhri, A; Rohimah, Siti (Proceeding of International Conference of Islamic Education, 2023)
Currently, tahfidz huts have mushroomed in every region, this is for consumption by parents now. However, the tahfidz boarding school combines memorization and technology applied to the tahfidz al-qur'an and IT darul fitrah Tawangsari Sukoharjo boarding schools. The application is not easy in the teaching and learning process between the two. In fact, there are not a few students who only tend to like technology and the reduced interest in memorizing students due to a lack of control from a teacher in teaching and learning. The purpose of this study was to determine the extent to which the teachers of the Darul Fithroh Grajegan Islamic boarding school had control, Tawangsari District, Sukoharjo Regency. also to find out the memorization of Islamic boarding school students Darul Fithroh Grajegan, Tawangsari District, Sukoharjo Regency. Conclusions based on the results of the research above, it is thus understood that there are other factors that can influence students' memorization of the Koran at the tahfidzul qur'an and IT Grajegan Tawangsari Sukoharjo Islamic boarding school, apart from the lack of teacher control, namely; students are less motivated in memorizing the Qur'an.